2011
DOI: 10.1634/theoncologist.2011-0145
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Underserved White Populations: The Case of Cancer-Related Disparities in Appalachia

Abstract: There are meaningful cancer-related disparities in the Appalachian region of the U.S. To address these disparities, the Appalachia Community Cancer Network (ACCN), a collaboration of investigators and community partners in five states (Kentucky, Ohio, Pennsylvania, Virginia, and West Virginia), is involved in increasing cancer education and awareness, conducting community-based participatory research (CBPR), and creating mentorship and training opportunities. The primary objective of this paper is to describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 24 publications
(25 reference statements)
1
58
0
Order By: Relevance
“…For all sites combined, Appalachia has higher rates of cancer regardless of sex, race, or region, consistent with previously reported findings (11,16,(18)(19)(20)(21)(22)(23). However, our data show that the gap has narrowed over time, with the exception of oral cavity and pharynx, larynx, lung and bronchus, and thyroid cancers.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…For all sites combined, Appalachia has higher rates of cancer regardless of sex, race, or region, consistent with previously reported findings (11,16,(18)(19)(20)(21)(22)(23). However, our data show that the gap has narrowed over time, with the exception of oral cavity and pharynx, larynx, lung and bronchus, and thyroid cancers.…”
Section: Discussionsupporting
confidence: 91%
“…Additional tobacco-related cancers that were elevated in Appalachia regions are urinary bladder, esophagus (men only), colon and rectum, cervix, and kidney and renal pelvis (women only). Other studies have shown varying results (16,18,19,23). CDC data show that among both males and females, the average smoking prevalence is higher for states in each Appalachian region compared with the United States (20% among males and 16% among females): 27% and 20% Southern region; 25% and 20% Central region; and 22% and 20% Northern region, among males and females, respectively (27).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[1][2][3][4] Although cancer of the lung and bronchus is elevated in Ohio Appalachia, the greatest disparity in incidence and mortality for smoking-attributable cancer is observed for cancer of the cervix. 4 Among Ohio Appalachian women, from 2000 to 2004, the average annual age-adjusted cervical cancer incidence rate was 9.7 per 100,000 and mortality rate was 3.4 per 100,000-rates 24.4% and 41.7% higher, respectively, than among non-Appalachian residing women.…”
Section: Introductionmentioning
confidence: 99%
“…(2) What is the distribution of smoking status (never, former, and current) by intimate partner and/or sexual GBV exposure among Ohio Appalachian women? (3) What is the association between cumulative exposure to a spectrum of intimate partner and/or sexual GBV abuse types and current smoking behavior among Ohio Appalachian women, accounting for other known risk factors for smoking among women in this region, including depression, age, and adult socioeconomic position?…”
Section: Introductionmentioning
confidence: 99%